THE EFFECTS OF DEPRESSION ON MENTAL HEALTH AND HYGIENE AT HIGHER LEVEL - Fareeda Saeed Pasha, Hafsa Nasir Khan, Maria Bibi (Pakistan Journal of Educational Research, 2022)
Education is the process of acquiring knowledge, developing skills of communication, analytical, problem-solving, and critical thinking accompanying the sense of responsibility regarding personal as well as societal. This study elaborates about the effect of depression on mental health and hygiene at higher level. Depression is the psychological phenomenon that unfavorably influencing on psychomotor, affection and cognitive domains. Depression is the crucial medical illness mood disorder that may express emotions of sadness, sorrow, or anger that obstruct on person’s everyday routine. The objective of this research was to identify the meaning of the term depression, types, causes, signs and symptoms, treatments and prevention regarding the effect of depression on mental health and hygiene. In the research, the targeted audience was the higher level students. The research was conducted by four universities of Karachi that are Jinnah University for Women (JUW), Bahria University, Karachi Medical and Dental College (KMDC), and NED University of Engineering and Technology and the sample size is (N=100) students. Descriptive research method was used and data was collected in quantitative research design through questionnaire tool. The result display that the rate of depression on adolescent is higher and it is influencing their mental health, physical health and social interactions that affecting their academic performances, behavior, interest, emotions,thoughts, personality, social and personal life.